Investigation of the impact of radiotherapy on the shoulder joint by ultrasonography in breast cancer patients - Karataş, Serdar; Alıcıoğlu, Banu (The European Research Journal, 2023)
Objectives: This study aimed to investigate the impact of radiotherapy (RT) on the supraspinatus, long head of the biceps and subscapularis tendons, and shoulder subcutenous fat tissue. Methods: Patients diagnosed with breast cancer who received RT to the anterior chest wall and axillary-supraclavicular region after breast-conserving surgery or mastectomy in our hospital. Overall, 56 (36 RT, 20 control group) patients were enrolled in this study. Pre-RT, post-RT 6-week, 3-month, and 6-month ultrasonographic and clinical assessments were performed. Results: The mean interval between surgery and RT was 5.6 (range: 2-8) months. Ten (27.7%) patients developed ultrasonographic abnormalities during the post-RT period. However, only 2 of these patients had shoulder pain and restricted range of motion in the shoulder. The thickness of the supraspinatus, biceps and subscapularis tendons were similar between the dominant and non-dominant sides of the control and RT group patients (5.7 mm vs. 5.1 mm, 2.87 mm vs. 2.89 mm, and 4.13 mm vs. 3.97 mm; respectively, p > 0.05). Thirteen patients were given RT on the ipsilateral side, and 23 received RT on the contralateral side. The pre-RT supraspinatus tendon thickness was significantly higher in the ipsilateral group than in the contralateral group (p = 0.026). However, there was no significant difference in the post-RT period (p = 0.408). Conclusions: In breast cancer patients undergoing adjuvant RT, RT may cause temporary edema in shoulder tendons. In addition, shoulder pain and restricted range of motion of the shoulder joint can be present in these patients.